Membentuk Akhlak Di Era Revolusi Industri 4.0 Dengan Peran Pendidikan Agama Islam - Munawir, Munawir; Salsabillah, Putriana; Rosyidah, Riysdatur (LP2M Universitas Islam Ahmad Dahlan, 2024)
Education has always been the main pillar in building national morals, including in the Industrial Revolution 4.0 era. The rapid development of technology has brought major changes in various areas of life, including education. This has a negative impact on the morals and character of society. On the one hand, this progress increases access and quality of education. The aim of this research was to clarify the role of Islamic religious education for students in this revolutionary era. This research uses a qualitative approach with a literature study research methodology. Islamic religious education provides a strong moral foundation in facing the challenges of the Industrial Revolution 4.0 era, where rapid change and technological advances can blur ethical and moral values. Islamic religious education not only helps students understand religious values, but also forms strong characters, making them honest, integrity and responsible individuals. This shows that Islamic religious education contributes significantly to social and moral development, which will ultimately support the creation of a more harmonious and prosperous society. Apart from the role of Islamic religious education, Islam also plays an important role in the formation of morals. Islam helps students understand religious values. Today's young generation must have high morals, be honest, believe in individuals, and contribute actively to society.